Assessment of N-acetylcysteine as an Alternative for the Treatment of the Premenstrual Dysphoric Disorder: A Randomized Clinical Trial - Fatemeh Rajabi; Monireh Haghanifar; Mohammad Javad Tarrahi (Journal of Pharmaceutical Care, 2020)
Introduction: Premenstrual dysphoric disorder (PMDD) is a common condition affecting females' quality of life in a significant negative manner. Verities of medical treatments have been investigated for whether the prevention or treatment of this condition with uncertain outcomes. The current stud has aimed to assess the efficacy of N-acetylcysteine (NAC) versus fluoxetine for the treatment of PMDD. Methods: The current randomized clinical trial has been conducted on 119 childbearing females, randomly divided into three groups of either treatment with 10 mg of fluoxetine twice daily or 450 mg of NAC twice daily or placebo in 2016-18. The participants used the agents for two weeks following menstruation. These treatment approaches performed for two menstrual cycles. The questionnaires of Hamilton and daily record of severity of problems (DRSP) were filled before and following the interventions for both groups, and the results were compared. Results: The baseline DRSP and Hamilton scores were not statistically different among the three groups(P-value>0.05) while by the end of the study all of the groups presented significantly improved scores(P-value<0.001). Comparison of three groups revealed remarkable inferiority of placebo to the other two groups(P-value<0.05) while no statistical difference was found between N-acetylcysteine with fluoxetine in terms of neither Hamilton(P-value=0.120) nor DRSP scores(P-value=0.749). Conclusion: The current study showed significant improvement in the PMDD symptoms following use of whether placebo or fluoxetine or NAC. Comparison of the agents revealed remarkable superiority of both fluoxetine and NAC to the placebo while NAC and fluoxetine had similar efficacy on the PMDD symptoms relief.